Antibiotics in water: Bean pods as adsorbent for removing and recovering ciprofloxacin - Jennifer Gubitosa; Domenico Cignolo; Vito Rizzi; Luca Pace; Paola Fini; Andrea Petrella; Chiara Milanese; Sara Paraboschi; Pinalysa Cosma (Environmental Chemistry and Ecotoxicology)
During this work, the Bean Pods are reported as adsorbent to remove Contaminants of Emerging Concern from water. Specifically, the Bean Pods were washed before their use with 1 M NaOH and HCl solutions, for activating their surface and rendering the material porous with a larger surface area, as evidenced by BET and SEM analyses. Indeed, the pods were fully characterized by adopting different techniques, and UV–Vis spectroscopy was adopted to monitor, at several contact times, contaminated water. To pursue this aim, Ciprofloxacin, a largely used antibiotic, was selected as a model contaminant, exhibiting an high absorption in the UV–Vis spectrum. Moreover, the roles of the physical and chemical parameters such as ionic strength, pH, adsorbent/pollutant amounts, and temperature, during the adsorption, were assessed, obtaining interesting information on the whole process, that occurred efficiently with a maximum adsorption capacity of 45 mg/g. The increase of the adsorbent amount (from 3 to 25 mg) and decrease of pollutant concentration (from 30 to 10 mg/L) favored the Ciprofloxacin removal due to the large presence of active sites. The change of pH values (i.e. 3, 6 and 12) and ionic strength values (in the range 0.001–0.5 M by adopting NaCl) largely inhibited the adsorption, evidencing the presence of electrostatic interactions. The adsorption isotherms, thermodynamics and kinetics of the process were also studied. Specifically, the Freundlich and Temkin models well described the process, suggesting the heterogeneous character of the adsorption, with the formation of a pollutant multilayer onto the adsorbent surface; the process occurred spontaneously (ΔG < 0) with an increase of entropy (ΔS > 0), and it was favored by the increase of temperature (ΔH > 0). The pseudo-first-order kinetic equation described the process with the applicability of the Weber-Morris model, denoting the key role of active sites to host the pollutant, and intraparticle diffusion, respectively. The recycling of the proposed adsorbent was successfully demonstrated by means of a salt solution. New horizons in the use of Bean Pods, for water remediation, was thus successfully demonstrated during this work, proposing an environmentally friendly approach for decontaminating water.